THE APPLICATION OF THE CHICKERING THEORY IN DEVELOPING UNDERGRADUATE STUDENTS’ EMOTIONS AND WELLBEING - Rukhaiyah Abd Wahab1,; Khairul Faiz Alimi,; Nur Azulia Kamarudin, (Journal of Islamic, Social, Economics and Development, 2024)
There were countless factors that caused undergraduates to experience tension, sadness, restlessness or even boredom during the 2020 Malaysia Movement Control Order (MCO). Unfortunately, these students did not know how to deal with problems and obstacles they encountered. If these concerns were not adequately handled, more psychological health difficulties could be faced by students, and these could impact their personal well-being. Therefore, this research tends to use Chickering Theory as a formal theory as students move to through seven vectors of the Chickering theory in facing those issues during the pandemic at UUM. The objective of this research is mainly to further understand the impact of Covid-19 on students’ emotions and their wellbeing specifically in dealing with teaching and learning processes. Hence, this research is very significant in the sense it can help in understanding students’ inner feelings and problems and finding ways to alleviate the problem through intervention from many parties such as UUM, lecturers, family and friends.